PENGKONSTRUKSIAN KURVA YIELD DENGAN METODE NELSON SIEGEL SVENSSON (Studi Kasus Data Obligasi Pemerintah) - Setyawati, Winda; Hoyi, Abdul (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2011)
Bond is one of fixed-income investment instruments because of their income granted a return for investor based on the interest rates predetermined. The level of cash that returns to the investors and factor which must be considered by investor before invest bond is called yield. The term stucture of interest rates gives the relationship between the yield on an investment and the time to maturity of the investment. The graphic depiction of the relationship between the yield on bonds in the different maturities is known as the yield curve. The yield curve contruction of the government bond with bond ID is FR (Fixed Rate) by Nelson Siegel Svensson models on the trade date 16 on February 2011. The data is obtained from Indonesian Stock Exchange (IDX). The parameter estimation is done by ordinary least square. The optimation function for its estimation is done by Nelder Mead simplex. Yield curve on day 16 depicted upward sloping. Â Keywords : Government Bond, Yield Curve, Fixed Rate, Nelson Siegel Svensson, Nelder Mead Simplex